A Model for Enhancing Digital Transformation through Technology‑related Continuing Professional Development Activities in Academic Libraries in Context - Nakaziba, Sarah; Ngulube, Patrick (Discover Education, 2024)
This paper is based on the findings of a doctoral study that aimed to examine the role of continuing professional development (CPD) in enhancing digital transformation in selected university libraries in Uganda. One of the ways of effecting digital transformation is to continuously build the technological competencies of the librarians working in academic institutions through attending technology-related CPD. The study adopted a mixed methods approach with a convergent parallel design for collecting qualitative and quantitative data from six universities in Uganda. Quantitative data were collected from 76 librarians with a minimum degree-level qualification from the six selected universities. Qualitative data were obtained from six University Librarians working in these universities. The study findings indicated several challenges hindering librarians from participating in technology-related CPDs such as lack of management support, lack of personal interest, limited funding, and lack of opportunities, among others. The implementation of digital transformation within university libraries in Uganda was also reported to be beset by a lack of competent staff, limited management support, lack of funds, and technological gaps. Therefore, this paper presents a proposed model to address challenges hindering the digital transformation and the participation in technology-related continuing professional development activities within academic libraries. The proposed model is based on the study findings, and it draws from Watkin and Marsick’s learning organisation model, andragogy theory, the technology-organisation-environment framework, and extant literature. The model will guide academic libraries in the implementation of a conducive environment to necessitate staff development and implementation of digital transformation.